Foreign direct investment and economic growth:Empirical study in the BRIC countries - Ling, Foo Sien (Universiti Malaysia Sarawak (UNIMAS), 2013)
The capital flows such as direct and portfolio flows has significant impact to countries economic growth. Foreign Direct Investment (FDI) has huge influence in create healthy financial markets with the positive impact towards the economic growth. The size of the capital flows become critical issues especially at the time liberalizing the capital account. The study attempts to examine empirically FDI and economic growth in the Brazil, Russia, India, and China (BRIC) countries. By using annual time series data for the period 1980 to 2011, FDI is positively affecting the economic growth direct contribution. The empirical analysis shows that FDI plays unambiguous role in contributing to economic growth in BRIC countries.